Pengaruh PDRB perkapita, jumlah wajib pajak dan inflasi terhadap penerimaan Pajak Bumi dan Bangunan (PBB) di Provinsi Sumatera Selatan - Sri Agustina; Didik Susetyo; Yunisvita Yunisvita (Jurnal Ekonomi Pembangunan, 2016)
This research was conducted to determine the effect of GDP, the number of taxpayers and inflation, on the land and building tax receipt (PBB). The data used in this study are secondary data from 2010-2015 the location of this study was conducted in Palembang City, Prabumulih City, Lubuk Linggau City and Pagaralam City. This research was conducted using analysis of Panel Least Square (PLS) Data Regression using Eviews 6.0. The results of this study indicate that GDP per capita, the number of taxpayers and inflation simultaneously affect the land and building tax receipt (PBB). Partially the GDP per capita variable and the number of taxpayers have a positive and significant effect on the PBB, while the inflation variable has a negative and not significant effect on the PBB). With the value of the Determination Coefficient (R2) of 0.990260 which means that the independent variable GDP Per capita, Number of Taxpayers and Inflation can explain the changes that occur in the UN dependent variable amounting to 99.02% while the other 0.98% are explained by other variables not included in the regression model